Telomere DNA G-quadruplex folding within actively extending human telomerase - Linnea I. Jansson; Jendrik Hentschel; Joseph W. Parks; Terren R. Chang; Cheng Lü; Rishika Baral; Clive R. Bagshaw; Michael D. Stone (2019)
Significance Telomeres protect the ends of linear chromosomes from illicit DNA processing events that threaten genome stability. Guanine-rich telomere DNA repeat sequences are protected by telomere-binding proteins, and are also prone to fold into structures called G quadruplexes (GQs). In highly proliferative cells, including the majority of human cancers, telomeres are maintained by the telomerase enzyme. Thus, telomerase and its telomere DNA substrates represent important targets for developing novel cancer drugs. The results of this study suggest GQ folding of newly synthesized DNA may occur within an actively extending telomerase enzyme. Our experiments highlight the importance of telomere DNA structure during the function of telomerase and its associated telomere-binding proteins.